Updatable Privacy-Preserving Reputation System based on Blockchain - Pilot, Matthias

A Formal Comparison of Advanced Digital Signature Primitives - Schürmann, Patrick

Designing Business Reputation Ecosystems — A Method for Issuing and Trading Monetary Ratings on a Blockchain - Hemmrich, Simon; Bobolz, Jan; Beverungen, Daniel; Blömer, Johannes (ECIS 2023 Research Papers)
Market transactions are subject to information asymmetry about the delivered value proposition, causing transaction costs and adverse market effects among buyers and sellers. Information systems research has investigated how review systems can reduce information asymmetry in business-to-consumer markets. However, these systems cannot be readily applied to business-to-business markets, are vulnerable to manipulation, and suffer from conceptual weak spots since they use textual data or star ratings. Building on design science research, we conceptualize a new class of reputation systems based on monetary-based payments as quantitative ratings for each transaction stored on a blockchain. Using cryptography, we show that our system assures content confidentiality so that buyers can share and sell their ratings selectively, establishing a reputation ecosystem. Our prescriptive insights advance the design of reputation systems and offer new paths to understanding the antecedents, dynamics, and consequences to reduce information asymmetry in B2B transactions.

Privacy-Preserving Collection and Evaluation of Log Files - Koch, Angelina

On the impossibility of surviving (iterated) deletion of weakly dominated strategies in rational MPC - Blömer, Johannes; Bobolz, Jan; Bröcher, Henrik

A Generic Construction of an Anonymous Reputation System and Instantiations from Lattices - Blömer, Johannes; Bobolz, Jan; Porzenheim, Laurens Alexander

Modelling and Proving Security for a Secure MPC Protocol for Stable Matching - Vahle, Ella

Bringing Structure to Structure-Preserving Signatures: Overview, Implementation and Comparison of Selected SPS Schemes - Siek, Hanna

On Transforming Lattice-Based Cryptography to the Ring Setting - Kramer, Paul

Evaluating database systems relying on secure multiparty computation - Anonymous, A

Cost of Privacy-preserving SMPC Protocols for NN-Based Inference - Anonymous, A

Privacy-Preserving Cryptography: Attribute-Based Signatures and Updatable Credentials - Eidens, Fabian

Cryptimeleon: A Library for Fast Prototyping of Privacy-Preserving Cryptographic Schemes - Bobolz, Jan; Eidens, Fabian; Heitjohann, Raphael; Fell, Jeremy

Issuer-Hiding Attribute-Based Credentials - Bobolz, Jan; Eidens, Fabian; Krenn, Stephan; Ramacher, Sebastian; Samelin, Kai (Cryptology and Network Security)

A Group Signature Scheme from Flexible Public Key Signatures and Structure-Preserving Signatures on Equivalence Classes - Schürmann, Patrick

Enhancing Security by Usage of Universal One-Way Hash Functions - Terfort, Tobias

Privacy-Preserving Incentive Systems with Highly Efficient Point-Collection - Bobolz, Jan; Eidens, Fabian; Krenn, Stephan; Slamanig, Daniel; Striecks, Christoph (Proceedings of the 15th ACM Asia Conference on Computer and Communications Security (ASIA CCS ’20),)

Comparison of Zero-Knowledge Range Proofs - Kramer, Paul

Rational Secure Multiparty Computation - Bröcher, Henrik

Efficient Finite-Field Arithmetic for Elliptic Curve Cryptography in Java - Pilot, Matthias

Implementation and Comparison of Elliptic Curve Algorithms in Java - Scholz, Swante

Updatable Anonymous Credentials and Applications to Incentive Systems - Blömer, Johannes; Bobolz, Jan; Diemert, Denis Pascal; Eidens, Fabian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security - CCS '19)
In this paper, we introduce updatable anonymous credential systems (UACS) and use them to construct a new privacy-preserving incentive system. In a UACS, a user holding a credential certifying some attributes can interact with the corresponding issuer to update his attributes. During this, the issuer knows which update function is run, but does not learn the user's previous attributes. Hence the update process preserves anonymity of the user. One example for a class of update functions are additive updates of integer attributes, where the issuer increments an unknown integer attribute value v by some known value k. This kind of update is motivated by an application of UACS to incentive systems. Users in an incentive system can anonymously accumulate points, e.g. in a shop at checkout, and spend them later, e.g. for a discount.

Practical, Anonymous, and Publicly Linkable Universally-Composable Reputation Systems - Blömer, Johannes; Eidens, Fabian; Juhnke, Jakob (Topics in Cryptology - CT-RSA 2018 - The Cryptographers' Track at the RSA Conference 2018, Proceedings)

Voronoi Cells of Lattices with Respect to Arbitrary Norms - Blömer, Johannes; Kohn, Kathlén (SIAM Journal on Applied Algebra and Geometry.)

Fully-Featured Anonymous Credentials with Reputation System - Bemmann, Kai; Blömer, Johannes; Bobolz, Jan; Bröcher, Henrik; Diemert, Denis Pascal; Eidens, Fabian; Eilers, Lukas; Haltermann, Jan Frederik; Juhnke, Jakob; Otour, Burhan; Porzenheim, Laurens Alexander; Pukrop, Simon; et al. (Proceedings of the 13th International Conference on Availability, Reliability and Security - ARES '18)
We present CLARC (Cryptographic Library for Anonymous Reputation and Credentials), an anonymous credentials system (ACS) combined with an anonymous reputation system. Using CLARC, users can receive attribute-based credentials from issuers. They can efficiently prove that their credentials satisfy complex (access) policies in a privacy-preserving way. This implements anonymous access control with complex policies. Furthermore, CLARC is the first ACS that is combined with an anonymous reputation system where users can anonymously rate services. A user who gets access to a service via a credential, also anonymously receives a review token to rate the service. If a user creates more than a single rating, this can be detected by anyone, preventing users from spamming ratings to sway public opinion. To evaluate feasibility of our construction, we present an open-source prototype implementation.

Cloud Architectures for Searchable Encryption - Blömer, Johannes; Löken, Nils (Proceedings of the 13th International Conference on Availability, Reliability and Security, ARES 2018)

Provably Anonymous Communication Based on Trusted Execution Environments - Blömer, Johannes; Bobolz, Jan; Scheideler, Christian; Setzer, Alexander
In this paper, we investigate the use of trusted execution environments (TEEs, such as Intel's SGX) for an anonymous communication infrastructure over untrusted networks. For this, we present the general idea of exploiting trusted execution environments for the purpose of anonymous communication, including a continuous-time security framework that models strong anonymity guarantees in the presence of an adversary that observes all network traffic and can adaptively corrupt a constant fraction of participating nodes. In our framework, a participating node can generate a number of unlinkable pseudonyms. Messages are sent from and to pseudonyms, allowing both senders and receivers of messages to remain anonymous. We introduce a concrete construction, which shows viability of our TEE-based approach to anonymous communication. The construction draws from techniques from cryptography and overlay networks. Our techniques are very general and can be used as a basis for future constructions with similar goals.

Models and Constructions for Secure Reputation Systems - Juhnke, Jakob

Enhanced Security of Attribute-Based Signatures - Blömer, Johannes; Eidens, Fabian; Juhnke, Jakob (The International Conference on Cryptology And Network Security (CANS))

Delegatable Attribute-based Anonymous Credentials from Dynamically Malleable Signatures - Blömer, Johannes; Bobolz, Jan (ACNS 2018 Applied Cryptography & Network security)
In this paper, we introduce the notion of delegatable attribute-based anonymous credentials (DAAC). Such systems offer fine-grained anonymous access control and they give the credential holder the ability to issue more restricted credentials to other users. In our model, credentials are parameterized with attributes that (1) express what the credential holder himself has been certified and (2) define which attributes he may issue to others. Furthermore, we present a practical construction of DAAC. For this construction, we deviate from the usual approach of embedding a certificate chain in the credential. Instead, we introduce a novel approach for which we identify a new primitive we call dynamically malleable signatures (DMS) as the main ingredient. This primitive may be of independent interest. We also give a first instantiation of DMS with efficient protocols.

Subtleties in Security Definitions for Predicate Encryption with Public Index - Blömer, Johannes; Liske, Gennadij (Proceedings of the International Conference of Mathematical Aspects of Computer and Information Sciences (MACIS))

CCA-Security for Predicate Encryption Schemes - Liske, Gennadij

Attribute-Based Encryption as a Service for Access Control in Large-Scale Organizations - Blömer, Johannes; Günther, Peter; Krummel, Volker; Löken, Nils (Foundations and Practice of Security)

Semantically Secure Attribute-based Searchable Encryption - Niehus, David

Instantiating a Predicate Encryption Scheme via Pair Encodings - Ganesh Athreya, Advait

Provably Secure Key-Derivation-Functions for Certain Types of Applications - Jürgens, Mirko

EAX - An Authenticated Encryption Mode for Block Ciphers - Diemert, Denis

Attribute-based Signatures using Structure Preserving Signatures - Bemmann, Pascal

Comparison of different Definitions of Chosen-Ciphertext Security in Encryption schemes - Porzenheim, Laurens

Commitment Schemes - Definitions, Variants, and Security - Bemmann, Kai Sören

Construction of Fully CCA-Secure Predicate Encryptions from Pair Encoding Schemes - Blömer, Johannes; Liske, Gennadij (Proceedings of the CT-RSA 2016)
This paper presents a new framework for constructing fully CCA-secure predicate encryption schemes from pair encoding schemes. Our construction is the first in the context of predicate encryption which uses the technique of well-formedness proofs known from public key encryption. The resulting constructions are simpler and more efficient compared to the schemes achieved using known generic transformations from CPA-secure to CCA-secure schemes. The reduction costs of our framework are comparable to the reduction costs of the underlying CPA-secure framework. We achieve this last result by applying the dual system encryption methodology in a novel way.

Physical attacks on pairing-based cryptography - Günther, Peter

Symmetric Anonymous Credentials with Protocols for Relations on Attributes - Hamm, Julian

Short Randomizable Aggregatable Signatures: Constructions and Security Analysis - Dallmeier, Fynn

Short Group Signatures with Distributed Traceability - Blömer, Johannes; Juhnke, Jakob; Löken, Nils (Proceedings of the Sixth International Conference on Mathematical Aspects of Computer and Information Sciences (MACIS))
Group signatures, introduced by Chaum and van Heyst [15], are an important primitive in cryptography. In group signature schemes every group member can anonymously sign messages on behalf of the group. In case of disputes a dedicated opening manager is able to trace signatures - he can extract the identity of the producer of a given signature. A formal model for static group signatures schemes and their security is defined by Bellare, Micciancio, and Warinschi [4], the case of dynamic groups is considered by Bellare, Shi, and Zhang [5]. Both models define group signature schemes with a single opening manager. The main difference between these models is that the number of group members in static schemes is fixed, while in dynamic schemes group members can join the group over time.

Implementierung eines hybriden Verschlüsselungsverfahrens nach Cramer und Shoup - Kalde, Benedikt

Protokolle zur authentifizierten Schüsselvereinbarung - Eisenhofer, Thorsten

Anonymous credential system based on q-Strong Diffie-Hellman Assumption - Eidens, Fabian

Anonymous and Publicly Linkable Reputation Systems - Blömer, Johannes; Juhnke, Jakob; Kolb, Christina (Proceedings of the 18th International Conference on Financial Cryptography and Data Security (FC))
Reputation systems are used to compute and publish reputation scores for services or products. We consider reputation systems where users are allowed to rate products that they purchased previously. To obtain trustworthy reputations, they are allowed to rate these products only once. As long as users rate products once, they stay anonymous. Everybody is able to detect users deviating from the rate-products-only-once policy and the anonymity of such dishonest users can be revoked by a system manager. In this paper we present formal models for such reputation systems and their security. Based on group signatures presented by Boneh, Boyen, and Shacham we design an efficient reputation system that meets all our requirements.

A Group Signature Scheme with Distributed Group Management - An Application of Threshold Encryption - Löken, Nils

A group signature scheme based on the LSRW assumption - Heihoff, Frederic

Evaluation of Pairing Optimization for Embedded Platforms - Sosniak, Martin

Elektromagnetische Seitenkanalangriffe auf paarungsbasierte Kryptographie - Gerken, Britta

Efficient Verifier-Local Revocation for Anonymous Credentials - Bobolz, Jan

Efficient Attributes for Pairing-Based Anonymous Credentials - Stroh, Christian

Constructions of Fully Secure Predicate Encryption Schemes - Schleiter, Patrick

Number of Voronoi-relevant vectors in lattices with respect to arbitrary norms - Kohn, Kathlén

Voronoi Cells of Lattices with Respect to Arbitrary Norms - Blömer, Johannes; Kohn, Kathlén
Motivated by the deterministic single exponential time algorithm of Micciancio and Voulgaris for solving the shortest and closest vector problem for the Euclidean norm, we study the geometry and complexity of Voronoi cells of lattices with respect to arbitrary norms.On the positive side, we show that for strictly convex and smooth norms the geometry of Voronoi cells of lattices in any dimension is similar to the Euclidean case, i.e., the Voronoi cells are defined by the so-called Voronoi-relevant vectors and the facets of a Voronoi cell are in one-to-one correspondence with these vectors. On the negative side, we show that combinatorially Voronoi cells for arbitrary strictly convex and smooth norms are much more complicated than in the Euclidean case.In particular, we construct a family of three-dimensional lattices whose number of Voronoi-relevant vectors with respect to the l_3-norm is unbounded.Since the algorithm of Micciancio and Voulgaris and its run time analysis crucially dependonthefactthatfortheEuclidean normthenumber of Voronoi-relevant vectors is single exponential in the lattice dimension, this indicates that the techniques of Micciancio and Voulgaris cannot be extended to achieve deterministic single exponential time algorithms for lattice problems with respect to arbitrary l_p-norms.

Tampering attacks in pairing-based cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Proceedings of Fault Tolerance and Diagnosis in Cryptography(FDTC))
In the last decade pairings have become an important, and often indispensable, ingredient in the construction of identity-based and attribute-based cryptosystems, as well as group signatures and credential systems. Consequently, the applicability of timing, power, or fault attacks to implementations of pairings is an important research topic. We will review some of the known results in this area.

RSA-Full Domain Hash Revisited - Rath, Timo
RSA Full Domain Hash ist im Zufallsorakelmodell ein EUF-CMA sicheres Signaturverfahren (existentially unforgeable under chosen-message attacks). Der Sicherheitsbeweis wird unter anderem in der Vorlesung Einführung in die Kryptographie vorgestellt. Auch bei einer genaueren Analyse verliert man bei der Reduktion einen Faktor \nicefrac{1}{q_{s}}(wobei q_{s}die Anzahl der Anfragen an das Signaturorakel darstellt), was für die Praxis in relativ großen Systemparametern (RSA-Modul) resultiert [1].Seit der Veröffentlichung von [2] wurde geglaubt, dass der Faktor \nicefrac{1}{q_{s}}optimal ist. Erst zehn Jahre später offenbarten die Autoren von [3] einen Fehler in [2] und zeigten eine bessere Reduktion allerdings unter einer etwas stärkeren Sicherheitsannahme.Die Ergebnisse aus [3] lassen sich auf PSS-Verfahren (Probabilistic Signature Scheme), das z.B. in PKCS #1 benutzt wird, übertragen und sind somit von großer Bedeutung für die Praxis. Weiterhin sind die in den Beweisen verwendete Techniken nützlich auch bei anderen kryptographischen Verfahren.In Rahmen dieser Arbeit sollen die entsprechenden Sicherheitsbeweise aufgearbeitet und dessen Auswirkungen für die Praxis analysiert werden.[1] J.S. Coron, “On the Exact Security of Full Domain Hash”, CRYPTO 2000. LNCS 1880, pp. 229-235, 2000.[2] J.S. Coron, “Optimal security proofs for PPS and other signature schemes”, EUROCRYPT 2002. LNCS 2332, pp 272-287, 2002.[3] S.A. Kakvi and E. Kiltz, “Optimal Security Proofs for Full Domain Hash, Revisited”, in EUROCRYPT 2012. LNCS 7237, pp 537-553, 2012.

Constructing CCA-secure predicate encapsulation schemes from CPA-secure schemes and universal one-way hash functions - Blömer, Johannes; Liske, Gennadij
We present a new transformation of chosen-plaintext secure predicate encryption schemes with public index into chosen-ciphertext secure schemes. Our construction requires only a universal one-way hash function and is selectively secure in the standard model. The transformation is not generic but can be applied to various existing schemes constructed from bilinear groups. Using common structural properties of these schemes we provide an efficient and simple transformation without overhead in form of one-time signatures or message authentication codes as required in the known generic transformations.

A Practical Second-Order Fault Attack against a Real-World Pairing Implementation - Blömer, Johannes; Gomes da Silva, Ricardo; Günther, Peter; Krämer, Juliane; Seifert, Jean-Pierre (Proceedings of Fault Tolerance and Diagnosis in Cryptography(FDTC))
Several fault attacks against pairing-based cryptography have been described theoretically in recent years. Interestingly, none of these have been practically evaluated. We accomplished this task and prove that fault attacks against pairing-based cryptography are indeed possible and are even practical — thus posing a serious threat. Moreover, we successfully conducted a second-order fault attack against an open source implementation of the eta pairing on an AVR XMEGA A1. We injected the first fault into the computation of the Miller Algorithm and applied the second fault to skip the final exponentiation completely. We introduce a low-cost setup that allowed us to generate multiple independent faults in one computation. The setup implements these faults by clock glitches which induce instruction skips. With this setup we conducted the first practical fault attack against a complete pairing computation.

Hiding software components using functional encryption - Jochheim, Janek

Group Signature Schemes with Strong Exculpability - Bemmann, Pascal

Fujisaki-Okamoto Transformation - Lippert, Jan

Verteilte Erstellung und Aktualisierung von Schlüsselservern in identitätsbasierten Verschlüsselungssystemen - Tezer, Alina

Seitenkanalresistenz paarungsbasierter Kryptographie - Otte, Oliver

Security Proofs for Pairing-Based Cryptography in the Generic Group Model - Bobolz, Jan

Securing Critical Unattended Systems with Identity Based Cryptography - A Case Study - Blömer, Johannes; Günther, Peter; Krummel, Volker (Proceedings of the 5th International Conference on Mathematical Aspects of Computer and Information Sciences (MACIS))
Unattended systems are key ingredients of various critical infrastruc-tures like networks of self service terminals or automated teller machines.For cost and efficiency reasons they should mostly run autonomously.Unattended systems are attractive and lucrative targets for various kindsof attacks, including attacks on the integrity of their components and thecommunication between components. In this paper, we propose a gen-eral cryptographic framework to protect unattended systems. We alsodemonstrate that instantiating the framework with techniques from iden-tity based cryptography is particularly well-suited to efficiently secureunattended systems.

Direct Chosen-Ciphertext Secure Attribute-Based Key Encapsulations without Random Oracles - Blömer, Johannes; Liske, Gennadij
We present a new technique to realize attribute-based encryption (ABE) schemes secure in the standard model against chosen-ciphertext attacks (CCA-secure). Our approach is to extend certain concrete chosen-plaintext secure (CPA-secure) ABE schemes to achieve more efficient constructions than the known generic constructions of CCA-secure ABE schemes. We restrict ourselves to the construction of attribute-based key encapsulation mechanisms (KEMs) and present two concrete CCA-secure schemes: a key-policy attribute-based KEM that is based on Goyal's key-policy ABE and a ciphertext-policy attribute-based KEM that is based on Waters' ciphertext-policy ABE. To achieve our goals, we use an appropriate hash function and need to extend the public parameters and the ciphertexts of the underlying CPA-secure encryption schemes only by a single group element. Moreover, we use the same hardness assumptions as the underlying CPA-secure encryption schemes.

Attributbasierte Verschlüsselung mittels Gittermethoden - Mathematische Grundlagen, Verfahren und Sicherheitsbeweise - Kohn, Kathlén

Identitätsbasierte Signaturen - Ein Sicherheitsbeweis für Signaturen auf Grundlage von Gap-Diffie-Hellman-Gruppen mit Hilfe des Forking-Lemmas - Löken, Nils

Identitätsbasierte Kryptographie - Implementierung von Paarungen für Körper der Charakteristik 2 - Haarhoff, Thomas

Attribute-basierte Verschlüsselung - Schleiter, Patrick

Fault attacks in pairing-based cryptography - Liske, Gennadij

Analyse und Evaluation eines identitätsbasierten Signcryption-Verfahrens - Liske, Gennadij